Cognitive impairment and depressive symptoms to predict renal outcome and mortality in older adult patients - Bokeung Peun; Ho Jun Chin; Jung-Yeon Choi; Kwang-il Kim; Heeseung Choi (PLoS ONE, 2026)
Cognitive impairment and depressive symptoms are common in older adults, but their impacts on adverse renal and survival outcomes remain unclear. This retrospective cohort study examined associations of cognitive impairment and depressive symptoms with renal replacement therapy (RRT) initiation and mortality among 5,191 adults aged ≥ 65 years. Cognitive impairment and depressive symptoms were assessed using the Korean Mini-Mental State Examination (MMSE-KC) and the Korean Short Geriatric Depression Scale (SGDS-K), respectively. During a mean follow-up of 45 months, 1,512 participants (29.1%) died and 68 (1.3%) initiated RRT. Depressive symptoms (SGDS-K score ≥ 5) were associated with increased risks of both incident RRT (HR 2.066, p = 0.004) and mortality (HR 1.565, p < 0.001). Cognitive impairment (MMSE-KC score ≤ 23) was associated with both incident RRT (HR 2.028, p = 0.007) and mortality (HR 1.728, p < 0.001). Subgroup analyses demonstrated that depressive symptoms remained associated with RRT risk across age groups and renal function strata, while cognitive impairment was linked to RRT primarily among those with preserved renal function or age < 75 years. Both factors were consistently associated with higher mortality across subgroups. Although receiver operating characteristic curve analysis showed comparable predictive value for RRT, cognitive impairment demonstrated greater discriminative ability for mortality. These findings suggest that depressive symptoms may serve as a relevant marker of renal deterioration requiring RRT, whereas cognitive impairment may more closely reflect mortality risk. Routine psychological and cognitive assessments may support early identification of high-risk patients and inform prevention strategies in geriatric care.